Specification for sprayed metal coatings Part 1. Protection of iron and steel by aluminium against atmospheric corrosion (BSI, 1964)
Metal coatings, Coatings, Protective coatings, Aluminium, Zinc, Metal spraying, Spraying (coating), Corrosion protection, Iron, Steels, Atmospheric corrosion, Surface treatment, Thickness, Symbols, Adhesion tests